2015
DOI: 10.1021/acs.jpcc.5b07764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica Surface Properties on the Formation of Multilayer or Submonolayer Protein Hard Corona: Albumin Adsorption on Pyrolytic and Colloidal SiO2 Nanoparticles

Abstract: The adsorption of bovine serum albumin (BSA) on two types of silica nanoparticles (NPs), one pyrolytic (P−SiO 2 ; namely AOX50 by Evonik) and the other colloidal (lab-made by using inverse micelles microemulsion, M−SiO 2 ), is studied. Both materials are characterized in terms of size of primary particles (by transmission electron microscopy), amounts (by thermogravimetry) and distribution of silanols (IR spectroscopy in controlled atmosphere, augmented by H/D isotopic exchange and reaction with VOCl 3 , to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 61 publications
(123 reference statements)
2
42
0
Order By: Relevance
“…40 Catalano et al reported an alpha helix content of approximately 36% for BSA adsorbed onto pyrolytic SiO 2 nanoparticles. 58 All previously reported results have a much lower content than what was measured in these studies, which can be due to the different nanoparticles used. Neither Lehman et al nor Catalano et al used water as the dispersant, 40,58 and Catalano et al reported that the media influence protein-nanoparticle interactions.…”
Section: Protein Secondary Structure As a Function Of Phmentioning
confidence: 54%
See 2 more Smart Citations
“…40 Catalano et al reported an alpha helix content of approximately 36% for BSA adsorbed onto pyrolytic SiO 2 nanoparticles. 58 All previously reported results have a much lower content than what was measured in these studies, which can be due to the different nanoparticles used. Neither Lehman et al nor Catalano et al used water as the dispersant, 40,58 and Catalano et al reported that the media influence protein-nanoparticle interactions.…”
Section: Protein Secondary Structure As a Function Of Phmentioning
confidence: 54%
“…58 All previously reported results have a much lower content than what was measured in these studies, which can be due to the different nanoparticles used. Neither Lehman et al nor Catalano et al used water as the dispersant, 40,58 and Catalano et al reported that the media influence protein-nanoparticle interactions. 58 The porosity of the nanoparticles may influence the adsorption of BSA to nanoparticle surfaces.…”
Section: Protein Secondary Structure As a Function Of Phmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, negligible electrostatic attraction between BSA and DOTAP has previously been observed at measured pH 6.5 . We, therefore, conclude that the physisorbed BSA molecules on the particle's surface effectively screen the negative charge of SiNP‐1 , thereby resulting in a weak interaction between SiNP‐3 (BSA) and the DOTAP shell.…”
Section: Resultsmentioning
confidence: 58%
“…In the case of nanomaterials (NMs) standardization is a particularly relevant issue. Numerous specific and non-specific factors have been shown to influence the results of toxicological testing [3], such as: i) the degree of dispersion of the NM, that varies depending upon the media used [4,5,6], ii) the real dose, that, oppositely to molecular substances may not correspond to the nominal one [7,8], iii) the presence of contaminants in the materials like bacterial lipopolysaccharides (LPS) [9] or metal ions [10] iv) the occurrence of artefacts due to adsorption of reagents or intrinsic absorbance/fluorescence of the material [3,11,12]. Much less explored is the effect of illumination during the preparation of samples and NM exposure in toxicological testing.…”
Section: Introductionmentioning
confidence: 99%